x/(a+b-c)=y/(b+c-a)=z/(c+a-b) show that =(x+y+z)/(a+b+c)
Answers
Answered by
0
Answer: i think this is what u are asking
Step-by-step explanation:
Let us see:
x/(a+b-c) = y/(b+c-a) = z(c+a-b) = k
=> x = ka+kb-kc —————————→ 1
and y = kb+kc-ka —————————→ 2
and z = kc+ka-kb —————————-> 3
add 1 and 3 above to get z+x = 2ka => (z+x)/a = 2k ————————-> 4
add 1 and 2 above to get x+y = 2kb => (x+y)/b = 2k ————————→ 5
add 2 and 3 above to get y+z = 2kc => (y+z)/c = 2k —————————→ 6
from 4, 5 and 6 above, we have (z+x)/a = (x+y)/b = (y+z)/c =====> PROVED
Similar questions